Methods, challenges and benefits of a health monitoring programme for Norwegian Olympic and Paralympic athletes: the road from London 2012 to Tokyo 2020 - Clarsen, B.; Steffen, K.; Moseby Berge, H.; Bendiksen, F.; Fossan, B.; Fredriksen, H.; Gjelsvik, H.; Haugvad, L.; Kjelsberg, M.; Ronsen, O.; Torgalsen, T.; Walløe, A.; et al. (British Journal of Sports Medicine, 2021)
Objective To describe the implementation of a health monitoring programme for Norwegian Paralympic and Olympic candidates over five consecutive Olympic and Paralympic Games cycles (London 2012, Sochi 2014, Rio de Janeiro 2016, PyeongChang 2018 and Tokyo 2020).